Thermodynamic Solvation of a-Amino Butyric Acid in Aqueous Mixture of Dipolar Aprotic N,N-Dimethyl formamide - Roy, S.; Mahali, K.; Akhtar, S.; Dolui, B.K. (Asian Journal of Chemistry, 2013)
Standard transfer free energies (DGt0(i)) and entropies (DSt0(i)) of a-amino butyric acid from water to aqueous mixture of cationophilic dipolar aprotic N,N-dimethyl formamide have been evaluated at 25 ºC from solubility measurements of the amino acid at five equidistant temperatures i.e., from 15 to 35 ºC. The chemical effects of the transfer Gibbs energies [DG0t,ch(i)] and entropies of transfer [TDS0t,ch(i)] have been obtained after elimination of cavity effect, estimated by the scaled particle theory and dipole-dipole interaction effects, computed by the use of Keesom-orientation expression. The chemical contribution of transfer energetics of a-amino butyric acid are guided by the composite effects of increased dispersion interaction, basicity effect and decreased acidity, hydrogen bonding effects, hydrophilic hydration and hydrophobic hydration of aqueous DMF mixtures as compared to that of reference solvent, water.